Analysis Of The Profitability Of Terasi Agroindustrial Busi-nesses In Puger District, Jember District - Ramadhani, Achmad; Nurdiana, Fefi; Aulia, Anisa Nurina (International Applied Science, 2024)
Fisheries management is all activities related to the utilisation of fish resources and the environment ranging from pre-production, production, processing to marketing processes carried out in a fisheries business system. One form of diversification of fishery products that is widely practised in Puger Wetan and Kulon villages in Puger District, Jember Regency is terasi product. The average profit of terasi agro-industry in Puger Kulon and Wetan villages in Puger District, Jember Regency has received a profit of Rp 45,121,274.91. The average break-even unit (BEP) of the shrimp paste fishing industry in Puger Kulon and Wetan villages in Puger District, Jember Regency is 219 Kg. The average break-even point (BEP) and the average break-even point (BEP) of acceptance of the shrimp paste fishing industry in Puger Kulon and Wetan villages in Puger District, Jember Regency is Rp 67,000,000.00 per production. The break-even point unit and acceptance (BEP) are above the break-even point and it can be concluded that the fishing industry in Puger Kulon and Wetan villages in Puger District, Jember Regency is profitable. In the agro-industry business of shrimp paste in the village of Puger Kulon and Wetan Puger District, Jember Regency has reached efficient. Based on the results of the R / C ratio analysis which shows that the average efficiency value, the production of agro-industry shrimp paste in the village of Puger Kulon and Wetan Puger sub-district is 3.16.